PERFORMA PETUGAS PADUAN SUARA MENGGUNAKAN METODE DEEPEEDI PADA UPACARA BENDERA DI SMPN 277 JAKARTA - Tyas Kartiko Sutawi; Andi Taslim Saputra (Universitas Negeri Makassar, 2022)
In addition to teaching, it is possible for teachers to have the additional task of guiding students outside of learning hours in the form of extracurriculars. Activities outside of class hours are intended to explore the potential of students beyond the subjects they are required to master. Padus Resisi is one of the extracurriculars that has potential. However, there are problems in Padus Resisi's routine training activities to become ceremonial officers every week. Based on initial observations, Padus Resisi has power , vocal technique, clothing appearance and attitude that need to be improved. This needs to be done so that the role of Padus Resisi as ceremonial officers can take place optimally. This study used a descriptive qualitative method. Data was collected using observation and interview techniques. The validity of the data is obtained by conducting data triangulation. In general, the collaboration of Demonstration, Peer Teaching and Drill (DeePeeDi) methods can be used as an innovative learning alternative in choral extracurricular learning. This method can help students master material including sound power, vocal techniques (articulation, phrasing and intonation), clothing appearance and student attitudes when singing.